PENGARUH TURBULENSI LINGKUNGAN, KNOWLEDGE SHARING BEHAVIOR, DAN STRATEGI INOVASI TERHADAP KINERJA USAHA KECIL MENENGAH KERAJINAN SEPATU KULIT DI MOJOKERTO - _, Rofiaty (Faculty of Economics and Business, University of Muhammadiyah Malang, 2011)
The research purpose is to analyze the impact between environment, knowledge sharing behavior, and inovation to the performance of leather shoes enterprise in Mojokerto, East Java. The analysis tool is multiple regression used a SPSS 16 program. The research results show the tested hypotheses, there are significant partial and simultaneous impact between environment , knowledge sharing behavior and inovation to performance. Knowledge sharing behavior as dominanly influence performance, which means SMEs must gain informations about competitor strategy to create product creativity & innovation, market trends & pole and product design to suit the customer behavior.